2015
DOI: 10.1016/j.jneuroim.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Activation and function of murine primary microglia in the absence of the prion protein

Abstract: The prion protein (PrP(C)) is predominantly expressed in the nervous and immune systems and is involved in relevant cell signaling. Microglia participate in neuroimmune interactions, and their regulatory mechanisms are critical for both health and disease. Despite recent reports with a microglial cell line, little is known about the relevance of PrP(C) in brain microglia. We investigated the role of PrP(C) in mouse primary microglia, and found no differences between wild type and Prnp-null cells in cell morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
8
1
Order By: Relevance
“…Such findings are in agreement with previous data obtained from immortalized microglia-like cell line, expressing or not PrP C , in which it was shown that PrP C expression alters TNF-α and IL-1β [ 134 , 135 ] or TGF-β and IL-10 [ 134 ] secretion. However, our results are in contrast with data obtained by Pinheiro et al, [ 136 ], reporting that genetic ablation of PrP C did not affect LPS-induced production of pro-inflammatory (TNF-α, IL-6, IL-1β) and anti-inflammatory (IL-10) cytokines.…”
Section: A Possible Role For Prp C In Neuroinflcontrasting
confidence: 99%
See 1 more Smart Citation
“…Such findings are in agreement with previous data obtained from immortalized microglia-like cell line, expressing or not PrP C , in which it was shown that PrP C expression alters TNF-α and IL-1β [ 134 , 135 ] or TGF-β and IL-10 [ 134 ] secretion. However, our results are in contrast with data obtained by Pinheiro et al, [ 136 ], reporting that genetic ablation of PrP C did not affect LPS-induced production of pro-inflammatory (TNF-α, IL-6, IL-1β) and anti-inflammatory (IL-10) cytokines.…”
Section: A Possible Role For Prp C In Neuroinflcontrasting
confidence: 99%
“…Unfortunately, even such studies aimed at elucidating PrP C function in microglial cells using PrP-KO models provided contradictory data. Indeed, while early studies on immortalized microglial cells suggested a key role for PrP C in microglial activation and regulation of the inflammatory response [ 134 , 135 ], more recent data, obtained in murine primary microglial cultures stimulated with LPS, reported no difference in cell morphology, microglial marker expressions and cytokine production between cells expression, or not, PrP C [ 136 ].…”
Section: A Possible Role For Prp C In Neuroinflmentioning
confidence: 99%
“…Tauroursodeoxycholic acid (TDUCA) is a bile acid produced in humans in small amounts and is approved by the US Food and Drug Administration to be safely used as a drug for human intake [13]. Cellular prion protein (PrP C ), a glycoprotein commonly known to pathogenically misfold into PrP SC (which causes neurodegenerative disorders [14,15]) plays vital metabolic roles in the body such as regulation of cell differentiation, cell migration, and long-term potentiation of synapses [[16], [17], [18]]. Furthermore, PrP C possesses a therapeutic function: it increases survival of MSCs, and one study has shown that PrP C is essential for reducing the oxidative stress at the injury site of an ischemia model [13].…”
Section: Introductionmentioning
confidence: 99%
“…The potential physiological functions of PrP C have been studied for over three decades, yet much debate persists regarding normal PrP C function and how it might impact prion pathogenesis. The cellular functions proposed to date for PrP C include regulation of copper metabolism, cell migration, cell differentiation, long term potentiation, cell survival, and inhibition of Bax mediated apoptosis 3 4 5 6 7 8 .…”
mentioning
confidence: 99%